Histone Demethylase AMX-1 Regulates Fertility in a p53/CEP-1 Dependent Manner - Ren, Xiaojing; Tian, Sisi; Meng, Qinghao; Kim, Hyun-Min (Frontiers in Genetics, 2022)
Histone methylation shapes the epigenetic configuration and adjusts multiple fundamental nuclear processes, including transcription, cell cycle control and DNA repair. The absence of histone demethylase LSD1/SPR-5 leads to progressive fertility defects as well as a reduction in brood size. Similarly, C. elegans LSD2 homolog AMX-1 has been implicated in regulating H3K4me2 and maintaining interstrand crosslinks (ICL) susceptibility. However, the mechanisms of how lack of AMX-1 induces sterility have not been addressed so far. This study investigated the histone demethylase AMX-1 in C. elegans and uncovered how amx-1 contributes to sterility in a p53/CEP-1 dependent manner. We show that while sterility in spr-5 mutants exhibited progressive over generations, amx-1 mutants displayed non-transgenerational fertility defects. Also, amx-1 mutants exhibited a reduced number of sperms and produced low brood size (LBS) or sterile worms that retain neither sperms nor germline nuclei, suggesting that fertility defects originated from germline development failure. Surprisingly, sterility exhibited in amx-1 was mediated by p53/CEP-1 function. Consistent with this result, upregulation of Piwi expression in amx-1 mutants suggested that AMX-1 is essential for germline development by regulating Piwi gene expressions. We propose that AMX-1 is required for proper Piwi expression and transposon silencing in a p53/CEP-1 dependent manner; thus, the absence of AMX-1 expression leads to defective meiotic development and sterility. This study elucidates how LSD2/AMX-1 contributes to sterility, therefore, expanding the boundaries of histone demethylase function.